2016
DOI: 10.1002/2015ja022127
|View full text |Cite
|
Sign up to set email alerts
|

Lidar observations of persistent gravity waves with periods of 3–10 h in the Antarctic middle and upper atmosphere at McMurdo (77.83°S, 166.67°E)

Abstract: Persistent, dominant, and large‐amplitude gravity waves with 3–10 h periods and vertical wavelengths ~20–30 km are observed in temperatures from the stratosphere to lower thermosphere with an Fe Boltzmann lidar at McMurdo, Antarctica. These waves exhibit characteristics of inertia‐gravity waves in case studies, yet they are extremely persistent and have been present during every lidar observation. We characterize these 3–10 h waves in the mesosphere and lower thermosphere using lidar temperature data in June f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
120
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(138 citation statements)
references
References 175 publications
(288 reference statements)
15
120
0
1
Order By: Relevance
“…Since there are relatively few observations or modeling studies of this region, comparisons of this amplitude with other work are scarce. Our perturbations are somewhat smaller than those used by Hickey et al () and in line with the relative perturbations found by Chen et al () Becker and Vadas () for the 90–110 km altitude ranges.…”
Section: Methodssupporting
confidence: 92%
“…Since there are relatively few observations or modeling studies of this region, comparisons of this amplitude with other work are scarce. Our perturbations are somewhat smaller than those used by Hickey et al () and in line with the relative perturbations found by Chen et al () Becker and Vadas () for the 90–110 km altitude ranges.…”
Section: Methodssupporting
confidence: 92%
“…The λ z range of 14–28 km is highlighted. This λ z range is chosen based on Figures and and consistent with the previous studies on the southern polar mesospheric IGWs (16 km in Suzuki et al [], 22–23 km in Chen et al [], and 20–30 km in Chen et al []). For GWs with trueω̂ = 2| f |−3| f |, the GWs are expected to have the λ h s of about 400–1000 km.…”
Section: Resultssupporting
confidence: 48%
“…Observed IGWs are in common characterized by near‐inertial intrinsic frequencies and large vertical wavelengths of more than 10 km. Chen et al [] analyzed in a rigorous and quantitative way the spectral characteristics of persistent IGWs with periods of 3–10 h observed at McMurdo, Antarctica, using lidar temperature in June for a period of 5 years. The persistent 3–10 h IGWs were found to have vertical wavelengths of 20–30 km and to be certainly differentiated from the global‐scale IGW modes (i.e., tidal waves), given that their vertical wavelengths are smaller than those of the high‐frequency tidal waves [ Smith et al , ; Du and Ward , ].…”
Section: Introductionmentioning
confidence: 99%
“…Except for the frequency and vertical wave number spectra in section 5, for the studies in sections 3 and 4, all the data sets longer than 12 h are divided into 12 h observational segments without overlaps in order to ensure reasonable statistics on gravity wave parameters while including gravity wave spectra as much as possible. As the inertial period at McMurdo is 12.24 h and gravity waves with periods of 3–10 h are persistently observed in the MLT region [ Chen et al ., ], 12 h segments are the best choice of window size in our case. In this process of division, if the remaining segment at the end has observational length less than 6 h, then this observational segment is abandoned.…”
Section: Methodsmentioning
confidence: 99%
“…The following procedure is implemented to estimate the gravity wave perturbations. As the inertia‐gravity waves (IGWs) with periods of 3–10 h are persistent and dominant in the McMurdo MLT region [ Chen et al ., , ; Chen and Chu , ] while the planetary waves (PWs) are clearly seen in the stratosphere [ Lu et al ., ; Chen et al ., ], this procedure aims to keep the IGW spectra as full as possible but significantly filter out PWs and tides.…”
Section: Methodsmentioning
confidence: 99%